Pelatihan Revisi Visi dan Misi Berdasarkan Rapor Pendidikan bagi Guru SD Inpres Lateri - Rehatta, Geradin; Manuhuttu, Silvia; Tomasoa, Theodora Florence (Universitas Pattimura, 2024)
Vision and mission revision training is an important aspect in developing the quality of education in elementary schools. This abstract presents a comprehensive overview of the study conducted on the community service process in vision and mission revision training based on education report card analysis for elementary school teachers. This study involves various stages, starting from an introduction to the importance of vision and mission revision to disseminating information to related stakeholders. This study introduces the importance of vision and mission revision training as an initial step in improving the quality of education. By identifying needs through analysis of education report card results, schools can determine areas that require improvement. The training process involving the selection of the right training team, interactive workshops, and mentoring, allows teachers to gain a deep understanding of the new vision and mission and the skills needed to apply them in daily practice. Evaluation of the implementation of the revised vision and mission is an important step in assessing its impact on the quality of education. This includes measuring teacher and student performance after implementation, as well as disseminating information to all related stakeholders. Overall, this study emphasizes the importance of collaboration, open communication, and involvement of the entire education community in improving the education system